Does Large Vessel Size Justify Use of Bare-Metal Stents in Primary Percutaneous Coronary Intervention?: Insights From the EXAMINATION Trial. (September 2019) - Costa, Francesco; Brugaletta, Salvatore; Pernigotti, Alberto; Flores-Ulmanzor, Eduardo; Ortega-Paz, Luis; Cequier, Angel; Iniguez, Andres; Serra, Antoni; Jiménez-Quevedo, Pilar; Mainar, Vicente; Campo, Gianluca; Tespili, Maurizio; et al.
Abstract : Background: Drug-eluting stents (DES) showed improved efficacy and safety compared with bare-metal stents (BMS), and international guidelines recommend their use as first line treatment. Yet, BMS are still widely used in practice, especially in large coronary vessels. We aimed to compare efficacy and safety of second-generation DES over BMS in large coronary culprit ST-segment elevated myocardial infarction lesions. Methods: We evaluated impact of large coronary stents (maximum size ≥3.50 mm) or smaller stents (<3.50 mm), among 1498 patients with ST-segment elevated myocardial infarction undergoing primary percutaneous coronary intervention, randomly allocated to everolimus-eluting DES or to an equivalent BMS platform in the EXAMINATION trial (Clinical Evaluation of the Xience-V Stent in Acute Myocardial Infarction Trial). Clinical events up to 5 years of follow-up were evaluated. Results: Large coronary stents were used in 683 patients (45.9%). At 5-year follow-up, the crude rate of the primary end point, a composite of all-cause death, any myocardial infarction, or any revascularization, was similar among patients treated with large or smaller coronary stents. The impact of DES versus BMS implantation was consistent irrespective of the stent size both for the primary end point ( P int =0.82) and other secondary ischemic end points. Within patients treated with bigger stents, DES implantation was associated to a trend toward a reduction of target lesion (hazard ratio, 0.53; 95% CI, 0.27–1.02; P =0.05) and target vessel revascularization (hazard ratio, 0.60; 95% CI, 0.34–1.03; P =0.066). Conclusions: Our results do not support the preferential use of BMS for patients with large coronary vessels. DES may warrant improved efficacy irrespective of stent size among patients undergoing primary percutaneous coronary intervention. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00828087. Abstract : Supplemental Digital Content is available in the text.